The prognosis prediction value of CD69+ CD8+ tissue-resident memory T cell as a novel indicator of pathologic complete response heterogeneity following different neoadjuvant therapy regimen in esophageal squamous cell carcinoma - Ao Liu; Defeng Liu; Xiuli Liu; Yuxiang Chi; Longxiang Guo; Dianxing Li; Qiankun Wang; Yuanlin Li; Yi Li; Guiwen Zheng; Haiqun Lin; Qiuan Yang; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Improving pathological complete response (pCR) rate is currently the main goal of neoadjuvant therapy for locally advanced esophageal squamous cell carcinoma (LA-ESCC). However, improved pCR rates do not consistently translate into better prognosis, likely due to regimen-specific pCR heterogeneity. We investigated this heterogeneity and potential biomarkers between two common neoadjuvant regimens. Methods We included 445 LA-ESCC patients from four centers, with 228 receiving neoadjuvant chemoradiotherapy (nCRT) and 217 undergoing neoadjuvant chemotherapy combined with immunotherapy (nICT). Propensity score matching ensured group comparability. We assessed pCR rates and their associations with overall survival (OS), disease-free survival (DFS), and recurrence patterns. Immune-related biomarkers were investigated through RNA sequencing and immune infiltration analysis, then validated via multiplex immunofluorescence staining. Results Overall, pCR was associated with significantly higher DFS (HR = 0.3 [0.18–0.5], P < 0.01) and OS (HR = 0.19 [0.08–0.41], P < 0.01) compared to non-pCR. The nICT group had a lower pCR rate than the nCRT group (27.2% vs. 42.9%) but demonstrated comparable prognosis and reduced distant metastasis. Among pCR patients, DFS was significantly better in the nICT group (HR = 0.2 [0.05–0.86], P = 0.031), with a trend toward improved OS. Immune analysis revealed increased CD8 + T cell infiltration, particularly CD69 + CD8 + tissue-resident memory T cells (TRM), in the nICT pCR group. The proportion of CD69 + CD8 + TRM cells was significantly linked to improved DFS (P = 0.016) and OS (P = 0.015), suggesting they may be superior prognostic markers compared to pCR rates. Conclusions The pCR obtained from different neoadjuvant treatments has distinct prognostic outcomes. The CD69 + CD8 + TRM, as a potential prognostic predictor, warrants further investigation.